Anemia as a Predictor of Transient Pacemaker Dependency After TAVI - Jaber, Mustafa; Khadija, Haitham Abu; Teodorovich, Nicholay; Ayyad, Omar; Gendelman, Gera; Poles, Lion; Diamante, Rafeal; Swissa, Moshe; George, Jacob; Blatt, Alex (International Journal of Innovative Research in Medical Science, 2022)
Background: Transcatheter aortic valve implantation (TAVI) has emerged as an effective and safe treatment for severe aortic stenosis in the last decades compared for surgical aortic valve replacement. However, it stills associated with high risk of conduction abnormalities requiring pacemaker implantation. Our study aimed to examine factors associated with transient conduction abnormities that don’t require pacemaker on long term. Methods: Retrospective analysis of all consecutive patients who underwent TAVI between 2010 and 2019 in Kaplan Medical Center, Rehovot, Israel. Results: Pre-TAVI haemoglobin levels were significantly lower in patients who developed transient CA compared to patients who develop persistent conduction abnormalities and were pacemaker dependent on follow up. Similarly, urea levels were higher in in patients with transient conduction abnormalities. Conclusion: Transient conduction abnormalities following TAVI are not uncommon. Correction of anaemia and volume depletion prior to TAVI may decrease the incidence of these transient conduction abnormalities and hence, decrease the fraction of unnecessary permanent pacemaker implantations in the long term. Watchful waiting may be wise in anaemic patients who develop CA after TAVI. The cut-off for haemoglobin levels prior to TAVI is yet to be determined.